Smart Durian Farming: IoT Based Tree and Fruit Fall Monitoring System - Mahathir, Muhamad Haiqal; Mat Nawi, Rosmamalmi (Applied Information Technology And Computer Science, 2025)
The Smart Durian Farming project addresses the challenges of traditional durian farming by developing an innovative Internet of Things (IoT)-based system that integrates advanced computer vision for orchard management. This project is essential because manual monitoring of durian farms is labour-intensive, inefficient, and prone to errors, leading to reduced fruit quality and yield losses from delays, animal interference, and environmental factors. The system combines tilt sensors and cameras to detect fruit falls in real time, cross-referencing data to enhance accuracy and reduce false positives. The solution is applied in large-scale durian farms, where it monitors tree health, provides immediate alerts for fallen fruits, and identifies threats such as animal activity. A web-based application ensures farmers can access real-time data and actionable insights from anywhere, streamlining farm operations and reducing manual labour. The expected result is a significant increase in productivity and profitability, as farmers can make timely, data-driven decisions. Additionally, the project supports sustainable farming practices by minimizing waste, optimizing resource usage, and paving the way for integrating future technologies such as automated irrigation and predictive yield analytics.